Analysis of the Impact of Indonesia's Membership in BRICS: Opportunities and Challenges in the Global Era - Mutia Salsabilla; Bambang Wahyu Nugroho (Journal of Social Research, 2025)
BRICS, comprising Brazil, Russia, India, China, and South Africa, represents over 40% of the world’s population, 25% of global GDP, and 17% of international trade. As a leading ASEAN economy, Indonesia’s membership offers opportunities for greater market access, foreign direct investment (FDI), and cooperation in technology and infrastructure. This research analyzes the impact of Indonesia’s BRICS membership on foreign policy and national growth using a qualitative, case study approach with data from literature reviews and online sources. Findings show that Indonesia’s formal membership, commencing on January 6, 2025, is a strategic effort to strengthen its global economic and political influence and counterbalance Western hegemony. Key benefits include expanded market access (non-oil and gas exports to BRICS reached $84.37 billion in 2024), investment diversification, technology collaboration, and alternative financing through the New Development Bank (NDB). Participation also enhances Indonesia’s negotiating leverage in international forums and aligns with its “free and active” foreign policy. However, challenges remain in maintaining diplomatic balance, particularly in managing differing interests among BRICS members (e.g., Russia and China) and addressing perceptions of bias toward certain Western blocs. Economic disparities and integration obstacles within BRICS also constrain cooperation. In conclusion, Indonesia must strategically manage its relations with both BRICS and Western partners while navigating internal dynamics to optimize the advantages of its membership.